Collection Development Policy in Academic Library - Zaki, Faddliza Mohd; Nasharudin, Nurhidayah (Perpustakaan Hamzah Sendut, 2016)
This paper aims to discuss on the collection development policy and its implementation that focused in academic library. The implementation will arises some issues and challenges. Academic library confronted the issue of budget and library is now moving towards e-book. The paper offers insights into how to overcome the issues and challenges faced. It describes the area in which collection development policy can be used to fulfill the critical roles of supporting the library’s mission to provide excellent resources, services and facilities in academic library.